Perlindungan Hukum Bagi Wajib Pajak Progresif Kendaraan Bermotor Di Provinsi Bali - Agung Ananda Putria Elda Sukawati; Luh Putu Suryani; Ida Ayu Putu Widiati (Warmadewa Press, 2021)
Vehicle tax is included in regional income that can support development through regional revenue and expenditure budgets. Progressive is a tax where the levy is by increasing taxes that must be paid in accordance with the provisions of the tax object. The purpose of this study is to determine the application of progressive tax on motor vehicle taxpayers in Bali Province and to determine legal protection for taxpayers against the imposition of progressive tax on motor vehicles in Bali Province. The method used is empirical legal research. The method used is empirical legal research. Sources of primary legal materials are obtained through research results and it can be concluded that the imposition of progressive vehicle tax can increase regional income towards motor vehicle tax (PKB) which is part of the Bali Province Regional Revenue and Expenditure Budget (APBD) which aims to improve the structure and infrastructure that support the welfare of the local communit. Reducing the number of private vehicle ownership for the community so that it can solve regional problems, namely congestion. Legal protection for progressive taxpayers is often a problem for vehicle owners, because people often do not report that the vehicle has changed hands.